Peran Robot dalam Novel Only Human Karya Sylvian Neuvel - Uci Amilah; Eva Dwi Kurniawan (Pusat Riset dan Inovasi Nasional, 2024)
The role of robots in the novel Only Human, focusing more on cultural aspects, behavior and geopolitical impacts. The aim of this research is to explore a deep understanding of the complexity of the relationship between humans and advanced technology and identify its ethical, social and geopolitical implications. The problem formulation includes questions about how humans respond to the presence of robots originating from different planets, what behavioral challenges arise in this relationship, and why cultural and ethical differences are important factors. The research method used is a hermeneutic approach to explore a deep understanding of the complex story in the novel. The results of this research tell about the role of robots in interacting with humans in various contexts and geopolitical changes between the planet and the earth. The role of robots in this novel also highlights the ethical and moral complexities in the use of advanced technology, as well as the challenges of the balance of power at the international level. Based on the results of the analysis, understanding and managing the impact of cultural and ethical differences in human interactions with robots, this research proposes considerations for designing international regulations which regulates the use of artificial intelligence in geopolitical and economic contexts. And aims to create an environment where technological developments can have a positive impact without sacrificing ethical and human values.